Technology into reality: Disentangling the challenges of shared autonomous electric vehicles implementation from stakeholder perspectives - Duan, Xu; Si, Hongyun; Xiang, Pengcheng (Energy (Oxford), 2025)
Shared autonomous electric vehicles (SAEVs) combine the advantages of shared mobility, electric and autonomous vehicles, revolutionizing the future of urban transport systems. SAEVs implementation should be supported by diverse stakeholders who are influenced and can influence its development. Therefore, this research aims to analyze the challenges of SAEVs implementation from stakeholder perspectives. According to a literature review and expert consultation, a list of seventeen challenges of SAEVs implementation considering stakeholders (i.e., users, legislators, operators and manufacturers) is compiled. Then, a combination of methods is utilized, including decision-making trial and evaluation laboratory (DEMATEL), interpretative structural modeling (ISM), and matrix impacts cross-reference multiplication applied to a classification (MICMAC). A hierarchical structure is created to reflect the interactions between challenges. Critical challenges at a deep level are cyber security and automation standards, and the direct challenges at a shallow level are testing and certification, travel preferences changing, and initial cost. In addition, the interrelationships between challenges are analyzed, and the most significant ones are identified. The practical implication guidelines for SAEVs development are formulated for various stakeholders to focus on critical challenges and developing proactive strategies. •Stakeholders involve users, legislators, operators and manufacturers.•17 challenges of SAEVs implementation from stakeholder perspectives are identified.•Critical challenges include CS and AS.•Direct challenges include TC, TPC, and IC.•IC, OC, FM, and PR have significant driving power, influencing other factors.